Social media: The influence of social networks on the perception of self-image of female adolescents (Research, Society and Development, 2022)
Physical appearance is increasingly becoming a social concern, especially for younger women in the population. In this sense, digital media play a leading role in the production and sharing of messages, content and information associated with food and body worship. Social networks have been a tool used by the media to propagate an ideal body pattern, which is, in most cases, unattainable. Thus, the present study aims to analyze the influence of social networks on the perception of the self-image of female adolescents. This is an integrative literature review, in which articles were searched in electronic databases: Google Scholar, Scielo, PubMed and Science Direct, published between 2012 and 2020, in Portuguese and English. After analysis, selection, eligibility and full reading of the articles, 10 eligible articles were selected that met the objective of this study. The results found show a prevalence of dominance of the aesthetic standards enunciated by the media, especially by social networks, in the perception of the self-image of female adolescents. It is concluded that it is extremely necessary that there is an educational dimension to the adolescent public, about conceptions related to body image, in order to enable them to have a critical look at the contents and possible inductions permeated by the media, in addition to make young people more receptive to their own bodies and less projective to models propagated by the media.